Cracks in the "Regulatory State". (September 2015) - Perrow, Charles
Over the last 30 years, the U.S. states has retreated from its regulatory responsibility over private-sector economic activities. Over the same period, a celebratory literature, mostly in political science, has developed, characterizing the current period as the rise of the regulatory state or regulatory capitalism . The notion of regulation in this literature, however, is a perverse one—one in which regulators mostly advise rather than direct, and industry and firm self-regulation is the norm. As a result, new and potentially dangerous technologies such as fracking or mortgage backed derivatives are left unregulated, and older necessary regulations such as prohibitions are weakened. This article provides a joint criticism of the celebratory literature and the deregulation reality, and strongly advocates for a new sociology of regulation that both recognizes and documents these failures.